2021
DOI: 10.1108/scm-12-2020-0641
|View full text |Cite
|
Sign up to set email alerts
|

Digital project driven supply chains: a new paradigm

Abstract: Purpose This paper aims to propose an integrated framework for digital project-driven supply chains (PDSC) to address multiple objectives in Architecture, Engineering, Construction and, Operations and Maintenance (AECO) value chain. Additionally, the following sub-objectives were also to be addressed: to assess emerging themes of Fourth Industrial Revolution (4IR) technologies in AECO and to identify lacunae in existing project supply chains. Design/methodology/approach The research relies on qualitative app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The use of augmented reality in SCM is expected to provide numerous benefits such as increased accuracy and efficiency in inventory management, improved customer satisfaction through real-time tracking of shipments, and reduced costs associated with errors in fulfillment (Akbari et al, 2022). In addition, augmented reality can provide a competitive advantage to companies that adopt it early (Bhattacharya and Chatterjee, 2022).…”
Section: Augmented Reality and Supply Chain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of augmented reality in SCM is expected to provide numerous benefits such as increased accuracy and efficiency in inventory management, improved customer satisfaction through real-time tracking of shipments, and reduced costs associated with errors in fulfillment (Akbari et al, 2022). In addition, augmented reality can provide a competitive advantage to companies that adopt it early (Bhattacharya and Chatterjee, 2022).…”
Section: Augmented Reality and Supply Chain Managementmentioning
confidence: 99%
“…Despite the numerous potential benefits, there are also some challenges associated with the use of augmented reality in SCM (Akbari et al, 2022). One of the biggest challenges is the lack of standardization in augmented reality technology, which makes it difficult to develop applications that can be used across different platforms (Bhattacharya and Chatterjee, 2022). In addition, the cost of augmented reality headsets and other hardware can be prohibitive for Brazilian Journal of Operations and Production Management, Vol.…”
Section: Augmented Reality and Supply Chain Managementmentioning
confidence: 99%
“…The AI effect is a phenomenon where actions once thought to require "intelligence" is frequently taken out of the definition of AI as machines grow more and more capable. For instance, despite being a commonplace technique, optical character recognition is typically left out of the list of items that are regarded to be AI [34].…”
Section: Fig-14 Artificial Intelligencementioning
confidence: 99%
“…Research has identified technologies that form a new industrial paradigm evolving around the use of digitalisation, connectivity, and automation. Specific examples of maturing and emerging technologies are 3D-printing (Meyer et al, 2020), digital twins (Schiele and Torn, 2020;Attaran, 2020), cyber-physical systems (Bhattacharya and Chatterjee, 2021), Internet of things (Legenvre and Gualandris, 2018), cloud computing (Manuel Maqueira et al, 2019), blockchain technology (Kurpjuweit et al, 2021;Schmidt and Wagner, 2019), big data analytics (Chen et al, 2015;Kache and Seuring, 2017), machine learning (Bohanec et al, 2017), and artificial intelligence (Baryannis et al, 2019;Toorajipour et al, 2021).…”
mentioning
confidence: 99%
“….0 0 a an nd d s sm ma ar rt t w wo or rk ki in ng g P PS SM M p pr ro of fe es ss si io on na al ls s Research has identified technologies that underpin a new industrial paradigm evolving from the use of digitalisation, connectivity, and automation. Specific examples of maturing and emerging technologies are 3D printing(Meyer et al, 2020), digital twins(Attaran, 2020), cyber-physical systems(Bhattacharya and Chatterjee, 2021), Internet of things(Legenvre and Gualandris, 2018), cloud computing (Manuel Maqueira et al, 2019), blockchain technology…”
mentioning
confidence: 99%